2019
DOI: 10.2106/jbjs.oa.19.00002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Magnitude of Limitations and Patient Experience During Recovery from Upper-Extremity Fracture

Abstract: Background:The relationship between the magnitude of limitations (measured by patient-reported outcome measures, or PROMs) and satisfaction with care providers and hospital services (measured by patient-reported experience measures, or PREMs) over the course of recovery after injury is unclear. The purpose of this study was to assess the relationship between a range of PROMs and 2 PREMs at 3 time points (initial office visit within a week, 2 to 4 weeks, and 6 to 9 months) after shoulder, elbow, and wrist fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The primary outcome was the decision process score of the knee decision quality instrument (K-DQI) questions 3.1 through 3.5 (eFigure in Supplement 2 ) ( Figure 2 ). 24 Secondary outcomes included the level of SDM (assessed using the CollaboRATE survey), 25 patient satisfaction with the consultation (numerical rating scale [NRS]), 26 condition-specific symptoms and functional limitations (KOOS JR), 27 duration of consultation in minutes, TKR rates (proportion of patients undergoing surgery), and treatment concordance (K-DQI question 1.6) (eFigure in Supplement 2 ). 24 All outcomes were assessed at the end of the clinical visit except KOOS JR and treatment concordance, which were assessed prior to the consultation and again at a follow-up appointment 4 to 6 months from initial consultation or date of TKR, as applicable.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome was the decision process score of the knee decision quality instrument (K-DQI) questions 3.1 through 3.5 (eFigure in Supplement 2 ) ( Figure 2 ). 24 Secondary outcomes included the level of SDM (assessed using the CollaboRATE survey), 25 patient satisfaction with the consultation (numerical rating scale [NRS]), 26 condition-specific symptoms and functional limitations (KOOS JR), 27 duration of consultation in minutes, TKR rates (proportion of patients undergoing surgery), and treatment concordance (K-DQI question 1.6) (eFigure in Supplement 2 ). 24 All outcomes were assessed at the end of the clinical visit except KOOS JR and treatment concordance, which were assessed prior to the consultation and again at a follow-up appointment 4 to 6 months from initial consultation or date of TKR, as applicable.…”
Section: Methodsmentioning
confidence: 99%
“…The different ways of obtaining data by telephone, online or in person, may however have introduced bias in the reported results. The same author 15 studied the relationship between a range of PROMs and the two PREMs mentioned above in patients with upper limb fractures. The study concluded that increasing alignment of PROMs and PREMs over the course of recovery after an upper-extremity fracture suggests that restored physical function may improve perceptions of satisfaction with care providers and hospital services over time.…”
Section: Discussionmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence (NICE) has published a quality standard that focuses on the patient experience 23 stating that “people using NHS services should be supported in shared decision making”. Patient's experiences have been investigated and utilised to identify disease processes that attenuate patient experience, 8 assess the relationship with validated PROMs 15 and validate predictors of health outcomes. 14…”
Section: Discussionmentioning
confidence: 99%
“…Asking to rate satisfaction of the process of care or treatment outcome may give different scores ( 29 ). Sixth, we did not perform separate analysis for different diagnoses because none of the diagnoses had sufficient numbers and—based on prior work—we did not feel diagnosis was likely to be important ( 30 , 31 ). Differentiating between preoperative and postoperative patients and between acute and chronic disorders may lead to different results.…”
Section: Discussionmentioning
confidence: 99%